PENGARUH PENERAPAN MODEL KOOPERATIF TIPE JIGSAWTERHADAP HASIL BELAJAR IPS SISWA DI SEKOLAH DASAR - Anzani, Usi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research is to find out. "The Effect of the Application of Jigsaw Cooperative Learning Model on Student Learning Outcomes of Students in Social Studies Learning in Class V of SD Negeri Gugus IV, Baso District, Agam Regency" This type of research is experimental research with experimental quasy design. The sample in this study were class V SDN Koto Gadang and SDN 12 Koto Tinggi. The results of the calculation of the research data which is the t-test obtained t count 13.8024> 1.68595 at the level of α 0.05. Thus it can be concluded that there is an effect of the application of Jigsaw cooperative learning model on student learning outcomes of students at social studies learning in class V SD Negeri Gugus IV, Baso District, Agam Regency.                                              Keywords:Jigsaw Cooperative, Student Learning Outcomes, IPS